Towards the Sustainable Exploitation of Salt-Tolerant Plants: Nutritional Characterisation, Phenolics Composition, and Potential Contaminants Analysis of Salicornia ramosissima and Sarcocornia perennis alpini - Lopes, Maria Celeste (2023)
Increasing soil salinisation represents a serious threat to food security, and therefore the exploitation of high-yielding halophytes, such as Salicornia and Sarcocornia, needs to be considered not merely in arid regions but worldwide. In this study, Salicornia ramosissima and Sarcocornia perennis alpini were evaluated for nutrients, bioactive compounds, antioxidant capacity, and contaminants. Both were shown to be nutritionally relevant, exhibiting notable levels of crude fibre and ash, i.e., 11.26–15.34 and 39.46–40.41% dry weight (dw), respectively, and the major minerals were Na, K, and Mg. Total phenolics thereof were 67.05 and 38.20 mg of gallic acid equivalents/g extract dw, respectively, mainly p-coumaric acid and quercetin. Both species displayed antioxidant capacity, but S. ramossima was prominent in both the DPPH and ß-carotene bleaching assays. Aflatoxin B1 was detected in S. ramosissima, at 5.21 g/Kg dw, which may pose a health threat. The Cd and Pb levels in both were low, but the 0.01 mg/Kg Hg in S. perennis alpini met the maximum legal limit established for marine species including algae. Both species exhibit high potential for use in the agro-food, cosmetics, and pharmaceutical sectors, but specific regulations and careful cultivation strategies need to be implemented, in order to minimise contamination risks by mycotoxins and heavy metals.